Amoeba plate test with Acanthamoeba castellanii as an innovative tool for Nocardia recovery from sputum samples: a proof-of-concept study - Coralie Espinasse; Ghislaine Descours; Marine Ibranosyan; Laetitia Beraud; Christophe Ginevra; Joelle Chastang; Oana Dumitrescu; Frédéric Laurent; Verónica Rodriguez Nava; Sophie Jarraud; Camille Allam (Microbiology Spectrum)
ABSTRACT Nocardia recovery from pulmonary samples is challenging due to the lack of a specific medium and the abundance of overgrown respiratory flora. This study aimed to compare the amoeba plate test (APT), an amoebic coculture with Acanthamoeba castellanii, with the axenic culture to recover Nocardia from pulmonary samples. Nocardia serial dilutions (n = 15 strains from seven species, concentrations ranging: 107–102 CFU/mL) in water and spiked overgrown sputa (n = 8) were simultaneously plated on agar with amoebic monolayer (APT) and without (control). Culture positivity rates, minimal growth concentrations, growth times, and abundance of flora overgrowth were compared for each condition. In water, Nocardia culture positivity rates were not significantly different between APT (86%, 30/35) and control (94%, 33/35; P = 0.246). In sputa, APT resulted in greater Nocardia growth (63%, 22/35 vs 37%, 13/35; P = 0.008). In addition, the elimination of interfering flora was more frequent using APT (34%, 12/35 vs 11%, 4/35; P = 0.01), and the overall abundance of flora was lower (median [interquartile range, IQR]: 1 [0–2] vs 3 [1-3]; P < 0.0001). The most grown species using APT were N. mexicana and N. otitidiscaviarum, whereas N. abscessus and N. nova were the most fastidious to grow under both conditions. This study reports Nocardia’s ability to grow in amoebic coculture, with some growth kinetic differences depending on the species, presumably implying their intra-amoebic multiplication. Furthermore, in APT, Nocardia recovery from overgrown sputa was greater, and flora decontamination was more effective. The present findings are strong arguments to implement APT as a complementary technique for Nocardia isolation from heavily contaminated samples.IMPORTANCEThe culture-proven diagnosis of Nocardiosis is challenging due to the difficulties in recovering Nocardia colonies from respiratory samples containing a complex polymicrobial flora. However, the isolation of Nocardia strains remains necessary to perform antibiotic susceptibility testing and adapt the antibiotic regimen of the patients. This study provides an innovative culture method based on a solid medium amoebic coculture, the amoeba plate test (APT), to cultivate Nocardia strains from clinical sputa samples. Nocardia grew across the APT amoebic monolayer. Moreover, the APT, which is already used in a reference center for the recovery of Legionella strains, exhibited good performances for Nocardia recovery and decontamination of interfering flora, thereby representing a promising second line tool to improve Nocardia culture.